(untitled) (Shaheed Smriti Journal, 2023)
The aim of the study is to explore the concept of elderly care in Nepalese society and its changing meaning in the modern times. Specially, this study tries to address the causes of old age homes are becoming a trend in Nepalese society. A cross sectional study was conducted mainly focusing on these facilities within the Kathmandu valley. A descriptive research design has been used whilst 18 elderlies who are living in private old age home were completed structured interviews for collecting data form three private owned old age home of Lalitpur and Kathmandu. The data were collected through the survey questionnaire analyzed with the help of SPSS software. Most of the respondents they are being there not only due to family’s member were abroad or migration or other issue. The trend of private old age home are becoming trend, whose family’s members are in Nepal but they were not properly cared from their children due to busy schedule that’s cause their families choosing this arrangement.